Achievement gap: Socioeconomic status affects reading development beyond language and cognition in children facing poverty. (October 2019) - Dolean, Dacian; Melby-Lervåg, Monica; Tincas, Ioana; Damsa, Crina; Lervåg, Arne
Abstract: Learning to read efficiently is one of the main skills that children has to learn in school and is important in order to functioning well in modern society. Even if children's reading skills seem to be related to their socioeconomic status, only a few studies have examined how SES is related to the development of reading skills in children facing severe poverty. This study traced 322 Roma children facing severe poverty from 7 through 9 years and compared them with an unselected sample of 178 Romanian non-Roma children. The Roma children had both poorer initial reading and a slower growth of their reading skills. In contrast to previous studies, SES did explain growth in reading skills after controlling for other well-known cognitive and linguistic predictors of reading. Among the Roma children, the effects of SES on reading growth were partly mediated by school absence. Thus, interventions directed at Roma children facing severe poverty need to target both the quality of reading instruction and broader aspects of these children's lives. Highlights: Roma children, the largest minority in Europe, live in poverty and are hard to reach in research. Roma children have lower levels and slower growth of early reading skills than their non-Roma peers. Socioeconomic status has a strong impact on how their reading start out and its development. Socioeconomic status affects school absence and language factors vital for early reading skills. Instruction should focus on early reading skills but also family engagement in education.